2019
DOI: 10.7759/cureus.4975
|View full text |Cite
|
Sign up to set email alerts
|

Management of Shallow Vestibule with Reduced Attached Gingiva in Fixed Prosthetic Intervention

Abstract: Shallow vestibule has long been considered a deterring factor in the use of removable dental prosthetics. The need for management in fixed prosthetic replacement is not widely discussed. Adequate attached gingiva is essential for continued proper oral hygiene. Muscular and fibrous traction leads to gingival recession, which can cause marginal leakage in a fixed prosthetic restoration. In the long-term, this causes the suprastructure to fail and, ultimately, the restoration also fails. Therefore, shallow vestib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 3 publications
0
7
0
Order By: Relevance
“…The main reason for having a shallow vestibule is ridge resorption following the extraction of tooth. Other factors relating to shallow vestibule can be firm muscle pull/insertion by positive frenal attachment [ 6 ]. This case presents as a gingival recession, which is because of the frenal pull in the lower anterior.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The main reason for having a shallow vestibule is ridge resorption following the extraction of tooth. Other factors relating to shallow vestibule can be firm muscle pull/insertion by positive frenal attachment [ 6 ]. This case presents as a gingival recession, which is because of the frenal pull in the lower anterior.…”
Section: Discussionmentioning
confidence: 99%
“…Also, the patient had a thin gingival phenotype and a shallow vestibule. Both can lead to the accumulation of plaque in the lower anterior and the possibility of having further recession in the lower anterior also increases [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
“…[11] Progressive bone loss in the edentulous maxilla or mandible creates issues with denture stability and placement. [12] Gingival margin binds better around teeth and implants with attached gingiva, which reduces inflammation around restored teeth [13]. A vestibular depth reduction may be caused by a long-term edentulous crest, an alveolar traumatism, or severe periodontitis.…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that gingival recession and inadequate width of keratinized gingiva are commonly associated with shallow vestibular depth and high attached muscle bers (23,24). Shallow vestibular depth prevents the insertion of removable prosthesis as well as compromises oral health control procedures (25). It also compromises the apical stability of graft tissue due to the greater effects of muscle attachment, and eventually causes graft shrinkage in the vertical dimension within one year after surgery.…”
Section: Introductionmentioning
confidence: 99%